2003
DOI: 10.1103/physrevlett.90.046401
|View full text |Cite
|
Sign up to set email alerts
|

Novel Optical and Magnetic Bistability and Photoinduced Transition in a One-Dimensional Halogen-Bridged Binuclear Pt Complex

Abstract: In iodine-bridged binuclear Pt compounds, R(4)[Pt(2)(pop)(4)I]nH(2)O and R(')(2)[Pt(2)(pop)(4)I]nH(2)O (pop=P(2)O5H2-2), electronic structures on the PtPtI chains have been controlled between a diamagnetic charge-density-wave (CDW) state and a paramagnetic charge-polarization (CP) state by modification of the counterions (R, R') located between chains. In the R=(C2H5)2NH+2 compound, a pressure-induced CP to CDW transition with a drastic color change is identified. This transition is accompanied by a large hyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 15 publications
3
46
0
Order By: Relevance
“…However, pop-type MMX chains are more attractive because it is easier to synthesize various derivatives by changing countercations. Moreover, the new electronic state [21], photo-induced phase transition [22] and vapor-induced reversible switching of the electronic state and the electrical conductivity [23][24][25][26] have been reported, recently. In order to achieve the higher electrical conductivity in pop-type MMX chains, the doping of hole or electron into 1D chain is a promising method, though no trials have succeeded.…”
Section: Open Accessmentioning
confidence: 99%
“…However, pop-type MMX chains are more attractive because it is easier to synthesize various derivatives by changing countercations. Moreover, the new electronic state [21], photo-induced phase transition [22] and vapor-induced reversible switching of the electronic state and the electrical conductivity [23][24][25][26] have been reported, recently. In order to achieve the higher electrical conductivity in pop-type MMX chains, the doping of hole or electron into 1D chain is a promising method, though no trials have succeeded.…”
Section: Open Accessmentioning
confidence: 99%
“…[6] In the former, the Pt-Pt dimer units are coordinated by four dithioacetate (dta) derivatives forming lantern structures, and these units are bridged by iodide ions to form neutral linear chains. The latter compounds have the chemical formulae A 4 [Pt 2 -(pop) 4 [7] We have also reported vapochromic behavior in {NH 3 (CH 2 ) n NH 3 } 2 [Pt 2 I(pop) 4 ]· 4H 2 O, which was accompanied by a phase change between the CP and CDW state with an increase or decrease in the temperature. [8] If a three-dimensionally ordered CP state can be constructed it may be possible to develop multiswitching devices, which convert between the CP state (ferroelectric, second-order optical nonlinear effect, paramagnetic) and the CDW state (non-dielectric, third-order optical nonlinear effect, diamagnetic) depending on pressure and photo and/or temperature-induced effects.…”
Section: Introductionmentioning
confidence: 99%
“…27,28) Here, we review the effect of the magnetic field on the PIPT and phase separation dynamics observed for spin crossover complexes as a typical example. We also review our recent work on ultra-fast dynamics of PIPT in 1/4-filled molecular crystals observed at around room temperature.…”
Section: Introductionmentioning
confidence: 99%